Aminah and aisha's eid gifts: ramadan and eid stories - Gilani-Williams, Fawzia; Jacobsen, Laura (Goodword Kidz New Delhi, India, 2007)
Everybody looks forward to the joyful celebrations of Eid. Amina and Aisha have such fun making a list of things they would like to present to others on this festival. Their surprise Eid boxes bring cheer and happiness into the hearts of the children receiving them